The Influence of Tourist Attraction on Revisit Intention at Karang Hawu Beach - Hamzah, Faizal; Ghani, Yosef Abdul; Pamungkas, Rio Septa Nugraha; Iskanda, Wisnu (Media Wisata, 2026)
Among its many attractions, Sukabumi Regency offers a wealth of cultural and natural wonders, which attract visitors with their enchanting charm. Karang Hawu Beach in Cisolok, Sukabumi, in particular, is renowned for its mysterious atmosphere associated with the myth of Nyai Roro Kidul, the queen of the southern coast. Although the number of tourist visits tends to increase, enhancing the attractiveness of the Karang Hawu destination through improved facilities and security measures can encourage repeat visits and support economic growth. The study findings underline the importance of attractions in influencing visitors’ intention to return, with a positive correlation observed between destination attractiveness and revisit intention. Enhancing the charm of the Karang Hawu destination in Sukabumi Regency is essential to attract and retain tourists. Recommendations for tourism managers include improving facilities, promoting natural beauty through social media, and fostering positive experiences to encourage repeat visits and word-of-mouth recommendations. Further research is recommended to explore additional variables or different settings within the same topic.